Elementos finitos para flexão de placas com campo de tensões assumido - Lima, Edison Castro Prates de (1972)
The development of two Hybrid Pian's formulation of the finite element method based on assumed stress distribution and applicable to plate-bending problem is presented. The former makes use of Reissner's theory for bending of "moderately thick" plates and the latter is based on the customary theory of elastic plates. As an application of the first formulation an element for "sandwich plates'' is developed. Listing of FORTRAN subroutines were included in the appendix. They can be used by any automatic program for structural analysis by finite element method.